Adapting to the global shortage of cholera vaccines: targeted single dose cholera vaccine in response to an outbreak in South Sudan. Issue 4 (April 2017) - Parker, Lucy A; Rumunu, John; Jamet, Christine; Kenyi, Yona; Lino, Richard Laku; Wamala, Joseph F; Mpairwe, Allan M; Ciglenecki, Iza; Luquero, Francisco J; Azman, Andrew S; Cabrol, Jean-Clement
Summary: Shortages of vaccines for epidemic diseases, such as cholera, meningitis, and yellow fever, have become common over the past decade, hampering efforts to control outbreaks through mass reactive vaccination campaigns. Additionally, various epidemiological, political, and logistical challenges, which are poorly documented in the literature, often lead to delays in reactive campaigns, ultimately reducing the effect of vaccination. In June 2015, a cholera outbreak occurred in Juba, South Sudan, and because of the global shortage of oral cholera vaccine, authorities were unable to secure sufficient doses to vaccinate the entire at-risk population—approximately 1 million people. In this Personal View, we document the first public health use of a reduced, single-dose regimen of oral cholera vaccine, and show the details of the decision-making process and timeline. We also make recommendations to help improve reactive vaccination campaigns against cholera, and discuss the importance of new and flexible context-specific dose regimens and vaccination strategies.